Kontribusi Kecerdasan Logik dan Minat Belajar Terhadap Prestasi Belajar Matematika - Nadun Nadun; Dian J Permana (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2014)
The purpose of this study was to determine the contribution of logical intelligence and interest in learning to Mathematics achievement. The method used in this study from survey and the study was conducted in SMA Depok municipality. Techniques used in the data collection done by using a questionnaire written test multiple choice test and questionnaire. Analysis of the data in this study using descriptive statistical methods with multiple regression testing.where this research results showed in: there is a significant influence jointly between logical intelligence variables (X1) and interest in learning (X2) on mathematics achievement (Y),which means learners have a good logical intelligence and has been interested in Mathematics will greatly affect the learning achievement in SMA Depok municipality